Clinico-haematobiochemical observations of induced acute nitrate toxicity in goats* - Mondal, D B; Pandey, N N (The Indian Journal of Animal Sciences, 2012)
Acute nitrate toxicity was induced in goats by single oral administration of 10% potassium nitrate @ 1.3 g/kg b.wt. Partial anorexia, mild depression, frequent muscle tremor, in-coordination, dyspnoea and brown discolouration of visible mucous membrane appeared from 2 hr onwards followed terminally by recumbency, salivation and colonic convulsions. The irreversible signs of toxicity appeared at 5.8Â±0.41 hr of toxicity when the animals were sacrificed. The haemato-biochemical alterations included significant decrease in haemoglobin, marked increase in methaemoglobin, nitrate and nitrite concentrations of plasma, urine and CSF and blood glucose alongwith significant rise in ammonia nitrogen of rumen liquor, cholesterol, urea nitrogen, creatinine and AST levels of serum. Diphenylamine blue test on blood, plasma, urine, CSF, rumen liquor and aqueous humor revealed strong positive reaction at the peak of toxicity. The CSF nitrite appeared to be of dependable diagnostic value since it truly reflected the nitrate toxicity.